Exploring Challenges and Opportunities: Investigating Perceptions and Attitudes of Students, Teachers, Principals and Parents towards Remote Learning in the UAE - ALBASTAKI, SHAIKHA ABDULHAMID (2024)
This research investigated the perspectives and experiences of the school community in the United Arab Emirates (UAE) regarding remote learning. Employing a conceptual framework informed by existing literature, the study sought to pinpoint essential elements for successful remote education and comprehend the support required for both students and educators. The participants encompassed a diverse range of stakeholders, including students, teachers, principals, and parents. Employing a mixed-method approach, which integrated qualitative and quantitative research methodologies, the study gathered and analyzed data to derive comprehensive insights. The findings obtained from the research highlighted a notable appreciation among participants for the flexibility offered by remote learning methodologies. However, despite this appreciation, there was an unmistakable inclination toThis research investigated the perspectives and experiences of the school community in the United Arab Emirates (UAE) regarding remote learning. Employing a conceptual framework informed by existing literature, the study sought to pinpoint essential elements for successful remote education and comprehend the support required for both students and educators. The participants encompassed a diverse range of stakeholders, including students, teachers, principals, and parents. Employing a mixed-method approach, which integrated qualitative and quantitative research methodologies, the study gathered and analyzed data to derive comprehensive insights. The findings obtained from the research highlighted a notable appreciation among participants for the flexibility offered by remote learning methodologies. However, despite this appreciation, there was an unmistakable inclination towards the traditional modality of face-to-face instruction. Furthermore, the results gained from the study illuminated an intriguing aspect pertaining to the current landscape of online educational practices, hinting at a tendency for knowledge transmission rather than transformative learning experiences. In light of these findings, the study advocates for the adoption of blended learning methodologies, which amalgamate the inherent advantages of both online and in-person teaching modalities. By integrating these approaches, blended learning stands poised to offer a more holistic and effective educational paradigm. Ultimately, this research serves as a beacon illuminating the landscape of online education within the unique context of the UAE, thereby proffering invaluable insights aimed at augmenting educational methodologies and practices in the region. wards the traditional modality of face-to-face instruction. Furthermore, the results gained from the study illuminated an intriguing aspect pertaining to the current landscape of online educational practices, hinting at a tendency for knowledge transmission rather than transformative learning experiences. In light of these findings, the study advocates for the adoption of blended learning methodologies, which amalgamate the inherent advantages of both online and in-person teaching modalities. By integrating these approaches, blended learning stands poised to offer a more holistic and effective educational paradigm. Ultimately, this research serves as a beacon illuminating the landscape of online education within the unique context of the UAE, thereby proffering invaluable insights aimed at augmenting educational methodologies and practices in the region.